Optimal short-term financing/investment decision under uncertainty - Mat, Hakan. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 1986., 1986)
This thesis aims at developing a solution procedure to the firms' short-term financing and investment decisions under uncertainty, In doing this, realizing the fact that the decisions related to a specific function of the firm have impacts on the others, an integrative approach is conducted First, different demand quantity forecasts depending on the envjronmental conditions the firm is operating, are generated for the current planning period. Secondly utilising a spreadsheet cash budget model cash requirements are determined as a result of collections, manpower, production, inventory, purchasing and payments planning for eachdemand forecast separately. Then, distributions of period cash requirements are obtained, Thirdly, a, linear programming model developed is used to obtain the optimal solutions to five different short-term financing/investment decision problems ranging from the most pessimistic to the most optimistic demand forecasts representing the Management's attitude towords risk. Opportunity cost and the optimality ranges of the cost coefficient and resource constants for conducting sensitivity analysis are also utilised as complementary parts of the optimal solutions. Finally, the optimal solutions are jnterpreted in terms of decisions, opportunity costs and optimality ranges and some guidelines to Management are deducted, In the study, the real-life data of a Turkish production firm is used.
Keywords: Working capital.; Investments.; Corporations -- Finance.